Review of Type III Endoleaks - Stoecker, Jordan B.; Glaser, Julia D. (Seminars in Interventional Radiology, 2020)
Endoleak remains a significant challenge to endovascular aneurysm repair, particularly as evolving techniques and devices have allowed treatment of increasingly complex aneurysm anatomy with increasing number of device components. Intervention is recommended for both type I and III endoleaks due to their risk of rupture, and endovascular techniques are the favored modality with placement of a bridging endograft over the endoleak defect. Conversion to open surgical repair remains the definitive option in cases where less invasive methods have failed or are precluded. In this article, the authors review evidence on the etiology, incidence, diagnosis, and current techniques for type III endoleak management.
Keywords: endoleak; aortic aneurysm; surgery; stent graft; interventional radiology; endovascular aneurysm repair